Media Penginderaan Jauh Berbasis Android dalam Pembelajaran Geografi SMA - Falik Wardana; Sugeng Utaya; Syamsul Bachri (Pascasarjana Universitas Negeri Malang, 2019)
Abstract: This research aims to determine the effectiveness of instructional media on Remote Sensing. Research on this multimedia following the steps Borg and Gall are modified, then have seven steps as needed. The effectiveness of media views of testing of products and comprehension test. The results of field trials demonstrate the effectiveness of the product amounted to 83.1% comprising the display aspect, materials, operations and language. In addition, the results of comprehension test by the students achieved a score with an average of 81.7 with a minimum completeness criteria 78. The level of school effectiveness and comprehension test scores can be categorized so effective that multimedia products eligible for use in learning. Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat keefektifan media pembelajaran pada materi Penginderaan Jauh. Penelitian terhadap multimedia mengikuti langkah-langkah Borg & Gall yang dimodifikasi, kemudian dipilih tujuh langkah disesuaikan dengan kebutuhan. Tingkat keefektifan media dilihat dari uji coba produk dan tes pemahaman. Hasil uji coba lapangan menunjukkan tingkat keefektifan produk sebesar 83,1% yang terdiri dari aspek tampilan, materi, pengoperasian dan bahasa. Selain itu hasil tes pemahaman oleh siswa mencapai skor dengan rata-rata sebesar 81,7 dengan kriteria ketuntasan minimal sekolah 78. Tingkat kefektifan dan skor tes pemahaman tersebut dapat dikategorikan sangat efektif sehingga produk multimedia layak digunakan dalam pembelajaran.